Implementation of Maqashid Sharia and Islamic Corporate Social Reponbility in Production Ethics (Case Study of Tempe Home Industry in Kamal Madura) - Mursyidi Abror (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
Islamic economics is an economic system that is built on the basics and arrangements of the Qur'an and Al-Sunnah with the aim of maslahah. Production does not only create something that does not exist, but also makes goods resulting from several productive activities that have usability. A producer must contain Islamic values in their production activities. This value is reflected in the objectives in the production cycle must containgood luck and uphold the ethics and norms of both parties, namely consumers and producers whose ultimate goal is to achieve happiness in the world and the hereafter (falah). This article discusses ethical issues related to tempe producers and their relation to religion. The literature review used includes the concept of ethics, production theory, Islamic production ethics and production in Islam. At the end of the discussion, namely how a tempe producer creates a mashlahah in their production activities by implementing the maqashid sharia concept and the concept of social responsibility in Islam (ICSR) from the tempe production activities so that their activities achieve Islamic values: barokah, maslahah, falah, responsibility. social responsibility that synergizes with production theory.